2006
DOI: 10.1139/z06-179
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intraclutch egg-mass variation and hatching asynchrony on relative offspring performance within broods of an altricial bird

Abstract: Rates of growth and size of nestlings at fledging have important consequences for future survival and reproductive success in many passerine birds. Within broods of altricial species, these characteristics are often influenced by size hierarchies established early in the nesting period due to hatching asynchrony and within-clutch variation in egg mass, but the concurrent effect of these factors is poorly understood. We investigated the relative influence of these variables on nestling performance within broods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 36 publications
(41 reference statements)
5
31
0
Order By: Relevance
“…Within clutches of tree swallows in my study, egg mass increased with laying order, which is in agreement with many previous studies of tree swallows (Zach 1982;Wiggins 1990;Ardia et al 2006;Bitton et al 2006; but see Whittingham et al 2007) and some other altricial species (Howe 1976;Ojanen 1983;Mead & Morton 1985;Hillstrom 1999;Saino et al 2004;Rosivall et al 2005;Liljesthrom et al 2012;Newbrey et al 2015). Like egg mass, yolk mass also increased with order of laying within clutches, as observed in previous studies of tree swallows (Ardia et al 2006), white-rumped swallows (Tachycineta leucorrhoa; Barrionuevo et al 2014), and red-winged blackbirds (Agelaius phoeniceus; Newbrey et al 2015), but in contrast to Chilean swallows (Tachycineta meyeni) for which size of yolk did not vary with laying order (Liljesthrom et al 2012).…”
Section: Egg and Yolk Masssupporting
confidence: 93%
See 4 more Smart Citations
“…Within clutches of tree swallows in my study, egg mass increased with laying order, which is in agreement with many previous studies of tree swallows (Zach 1982;Wiggins 1990;Ardia et al 2006;Bitton et al 2006; but see Whittingham et al 2007) and some other altricial species (Howe 1976;Ojanen 1983;Mead & Morton 1985;Hillstrom 1999;Saino et al 2004;Rosivall et al 2005;Liljesthrom et al 2012;Newbrey et al 2015). Like egg mass, yolk mass also increased with order of laying within clutches, as observed in previous studies of tree swallows (Ardia et al 2006), white-rumped swallows (Tachycineta leucorrhoa; Barrionuevo et al 2014), and red-winged blackbirds (Agelaius phoeniceus; Newbrey et al 2015), but in contrast to Chilean swallows (Tachycineta meyeni) for which size of yolk did not vary with laying order (Liljesthrom et al 2012).…”
Section: Egg and Yolk Masssupporting
confidence: 93%
“…In addition, these nestlings could possibly benefit from having a greater immune response than their older siblings by having a greater amount of carotenoids (Bortolotti et al 2003) and immunoglobulins (Graczyk et al 1994) from their larger yolks. This suggests that female tree swallows in my study population follow a "brood survival" strategy (Slagsvold et al 1984), as has been indicated for other tree swallow populations (Wiggins 1990;Ardia et al 2006;Bitton et al 2006). …”
Section: Egg and Yolk Masssupporting
confidence: 73%
See 3 more Smart Citations